Determination of 5-hydroxymethylfurfural (HMF) by means of flow-through analyzer. - J. ŠAVEL; K. PAZOUREK (Kvasný průmysl, 2001)
The article deals with the determination of 5-hydroxymethylfurfural in intermediates and beer during its production and storage by means of SKALAR flow-through analyzer. The determination is based on the classic Winkler's method with barbituric acid and p-toluidine after precious separation of HMF in a dialyzer unit. In the work, HMF contens were monitored in laboratory wort, hopped wort, hopped wort under fermentation and ready bottled beer in the course of its aging. The content of HMF in bottled beer was increasing in course of storage, this was also dependent on the type of beer. The changes in HMF content that were found were in agreement with literary data and the measurement can be used for current control applications to monitor the course of mashing, boiling and hopped wort cooling fermentation and aging of beer. The method enables handing up to 25 samples in one hour.(In Czech, English summary only)